The Journey Home- Guiding Intangible Knowledge Production in the Analysis of Ancestral Remains (Final Report) - Schaepe, David M.; Rowley, Susan; Stó:lō Xyolhmet S’olhetawtxw Sq’éq’ip (Stó:lō House of Respect Committee) Members; Weston, Darlene; Richards, Mike (Simon Fraser University, 2015)
The final report from the Journey Home Project, an IPinCH Community Initiative.